Comparisons of Chemical Profiles and Gastroprotective Effects of Citri Sarcodactylis Fructus Pre- and Poststeam Processing. (23rd September 2020) - Zhu, Yinji; Zhang, Qiuxia; Gao, Ming; Wang, Hongfei; He, Hui; Wang, Jinyu; Chen, Kang
Abstract : Background . Citri Sarcodactylis Fructus (CSF) is widely used as folk medicine in traditional Chinese medicine (TCM). The dried and steam-processed CSF (SCSF) has been employed for harmonizing the stomach over thousands of years under the guidelines of TCM theory. However, little is known about the differences in chemical compositions between CSF and SCSF. Moreover, the gastroprotective effects of CSF and SCSF on ethanol-induced gastric mucosal injuries in rats have yet to be investigated. Consequently, the present study aimed to investigate the chemical differences and gastroprotective effects of CSF and SCSF, providing some experimental framework for the development of CSF and SCSF. Methods . The chemical compositions of CSF and SCSF extracts were determined using an ultra-performance liquid chromatography-quadrupole time-of-flight mass spectrometer (UPLC-Q-TOF-MS), and their gastroprotective effects of different doses were assessed in rats with ethanol-induced gastric injuries on the levels of oxidative stress and inflammatory cytokines. Results . A total of 42 components were identified in CSF and SCSF, and most of them were flavonoids, limonoids, coumarins, and glycosides. There were no differences in the compositions between CSF and SCSF, but the relative contents of the components were different. Among them, nine screened compounds were considered as potential discriminating markers responsible for the differences between CSF and SCSF. Besides, pretreatments with CSF and SCSF markedly improved the gastric mucosal injuries in rats for their antioxidant and anti-inflammatory properties. And SCSF exhibited a better gastroprotective effect than CSF. Conclusion . The compositions of CSF were unchanged after steam-processing, while the relative contents of their components were changed. These changes may be the major reasons for the differentiation of their efficacies. In addition, CSF and SCSF could alleviate ethanol-induced gastric mucosal injury through the enhancement of antioxidant and anti-inflammatory activities. SCSF exhibited a better gastroprotective effect than CSF, which emphasized the necessity of steam processing.